PENGARUH EFEKTIVITAS KOMITE AUDIT TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2013) - Diori Novade; Herry Laksito (Diponegoro Journal of Accounting, 2015)
The purpose of this study is to examine the effect of audit committee effectiveness and timeliness of  reporting on non-financial companies listed on the Indonesia Stock Exchange in 2013. DeZoort index divides the effectiveness of audit committees form the four elements: composition, authority, resources, and diligence. Those elements are examined one by one: the audit committee expertise,  the audit committee size and the audit committee meeting. The population in this study are all non-financial companies listed on the Indonesia Stock Exchange in 2013. Samples are obtained as many as 260 companies that have the completeness of the data needed by using purposive sampling. The data used is secondary data that is audited annual report on non-financial company in 2013 and contains the date of publication of the financial statements. This study uses logistic regression analysis. The results of this study indicate that the audit committee expertise, the audit committee size and audit committee meetings significantly effect on the timeliness of financial reporting.